2014
DOI: 10.5194/hess-18-4751-2014
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of transit time distributions, mean transit times and their relation to catchment topography

Abstract: Abstract. The transit time of water is a fundamental property of catchments, revealing information about the flow pathways, source of water and storage in a single integrated measure. While several studies have investigated the relationship between catchment topography and transit times, few studies expanded the analysis to a wide range of catchment properties and assessed the influence of the selected transfer function (TF) model. We used stable water isotopes from mostly baseflow samples with lumped convolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
161
5

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(176 citation statements)
references
References 45 publications
10
161
5
Order By: Relevance
“…It is increasingly recognised that stable isotopes cannot provide realistic estimates of longer TT waters, regardless of the lumped model used Seeger and Weiler, 2014;Kirchner, 2015). In this study, it is very likely that older water (i.e.…”
Section: Identification Of a Younger Component In Streamflowmentioning
confidence: 90%
See 3 more Smart Citations
“…It is increasingly recognised that stable isotopes cannot provide realistic estimates of longer TT waters, regardless of the lumped model used Seeger and Weiler, 2014;Kirchner, 2015). In this study, it is very likely that older water (i.e.…”
Section: Identification Of a Younger Component In Streamflowmentioning
confidence: 90%
“…In an earlier study, Stewart et al (2007) reported differences of up to an order of magnitude between the TTs determined using stable isotopes as compared to those determined using tritium ( 3 H). Later works by Seeger and Weiler (2014) and Kirchner (2015) reinforced the point that "stable isotopes are effectively blind to the long tails of TT distributions" (Kirchner, 2015). The effects of older groundwater contributions to streamflow have largely been ignored until recently (Smerdon et al, 2012;Frisbee et al, 2013), and according to Stewart et al (2012), new research efforts need to be focused on relating deeper groundwater flow processes to catchment response.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several distribution types have been used in catchment studies, including the dispersion model (Kirchner et al, 2001;McGlynn et al, 8 2003;McGuire et al, 2002), the piston flow model (McGlynn et al, 2003), and exponentialpiston flow (Maloszewski and Zuber, 1996;McGlynn et al, 2003;McGuire et al, 2002;Timbe et al, 2014). The exponential distribution has been the most widely used (more than 60% of the studies in several recent reviews; McGuire and McDonnell, 2006;Mueller et al, 2013;Roa-Garcia and Weiler, 2010;Seeger and Weiler, 2014), though more recently, the gamma function has been recognized as more conceptually and mathematically suitable to represent catchment behaviour and mixing processes due to its short breakthrough time and long tail (Birkel et al, 2012;Dunn et al, 2010;HeidbĂŒchel et al, 2012;Hrachowitz, 2011;Hrachowitz et al, 2010;Kirchner et al, 2001Kirchner et al, , 2000Soulsby et al, 2011).…”
Section: Time Distribution Terms and Conceptsmentioning
confidence: 99%